Determinants of change in household level of consumption and poverty in Uganda, 1992/93 - 1999/00 - Benin, Samuel; Mugarura, Samuel (International Food Policy Research Institute, 2005)
Recent estimates showing increase in the incidence of poverty in Uganda has kindled interest in understanding the factors that cause changes in poverty, as the reversal of the positive trend in the 1990s threatens the government’s poverty eradication plan of reducing poverty to a level below 28% by 2014. Using a household and community panel dataset, this paper analyzes the factors contributing to change in household-level consumption and poverty.